Evaluation of Sorghum bicolor (L.) Moench on the Reduction of Creatinine Levels and Its Antioxidant Properties In vitro - Obika, Ogochukwu Immaculate; Oyawaluja, Aminat Asabi; Oiseoghaede, Joseph O; Odukoya, Olukemi Abiodun; Ndiri, Ngozi Afulenu Obika (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The study investigated the effect of Sorghum bicolor (L.) Moench extract on the renal activity of both normal and ailing patients. Phytochemical analysis, antioxidant activity, vacuum liquid chromatography and TLC were carried out. The creatinine reduction ability was analyzed using Jaffe’s method for clean-catch spot urine samples of normal, diabetic and hypertensive patients. S. bicolor showed strong antioxidant activity with an IC50 value of 52.17 μg/ml, compared to the standard vitamin C with an IC50 value of 40.59 μg/ml. Statistical analysis (ANOVA) result showed a significant difference between the patients’ urine (rows) (p-value = 2.77×10–08) and a significant difference between the dose treatments (columns) (p-value = 8.38×10–14). Whilst different fractions of S. bicolor at different concentrations showed varying effects on the creatinine concentration, it reduced creatinine level in low doses and has antioxidant properties. Dhaka Univ. J. Pharm. Sci. 21(2): 165-172, 2022 (December)